Foodborne illness outbreak in a special population. Cali, Colombia 2021. - Osorio Merchan, May Bibiana; Rizo-Tello, Victor Zein; Sánchez León, Edna Margarita; Arturo Quiroga, Gabriela Lizeth; Prieto-Alvarado , Franklyn Edwin; Gómez Ortega, Luis Carlos (Interdisciplinary Journal of Epidemiology and Public Health, 2021)
Introduction: Foodborne Diseases have a high impact on confined populations with poor conditions in the preparation and distribution of food. In May 22 of 2021, the SAT Early Warning System of (In Spanish, Sistema de Alerta Temprana) the National Health Institute detected an outbreak in Cali in a closed population. Objective: Characterize the outbreak of Foodborne Diseases (In Spanish ETA) in a specific population of Cali, and identify the source, agent, and transmission mechanism to guide control measures. Methods: Outbreak investigation through consumer survey and analysis with case-control methodology. Food safety analysis and laboratory studies of cooked food were carried out. Three case definitions were created. Epi info 7.4.2 was used and the three definitions by OR were contrasted: Food, place of consumption, shift of consumption, age and sex. Results: 140 cases of 1,600 exposed people were identified, attack rate of 8.8%. Average incubation period of 11.7 hours, minimum of 2.5 hours and a maximum of 23 hours. It was identified that the later the food was consumed, the sicker there were. Dinner caused the largest proportion of patients, with OR 8.19,95% IC: 1.8-36.1. In post-outbreak food matrix analyzes, E. coli and total coliforms were isolated. Conclusion: It is considered that the source was the dinner consumed on May 20, 2021, the agent an E. coli toxin, and the most likely mechanism of transmission was cross-contamination.